ANALISA TOTAL PRODUCTIVE MAINTENANCE MESIN CINCINNATI DI PT. DIRGANTARA INDONESIA - Astuti, Marni (SENATIK STT Adisutjipto, 2016)
The creation of a good product PT. DIRGANTARA INDONESIA assisted with production machines, one of which is the machine CNC MACHINE (DOUBLE CINCINNATI Milacron gantry ALUMINIUM TYPE-F), the role of a machine type-f CNC machine itself is very influential in the existing production process at PT. DIRGANTARA INDONESIA. The lack of treatment systems for the repair and replacement of components caused because the machines that is already beyond the age of many techniques, resulting in the production of the company to become unstable.In this study used methods Overall Equipment Effectiveness (OEE) and the concept of autonomous maintenance and using Failure Mode and Effect Analysis (FMEA) to determine analyze potential errors or failures, it is advisable to keep using autonomous maintenance as minor maintenance.            Analysis and discussion of the results obtained OEE decline in 2014 to 2015 is 86.15% to 75.62% drop is due to the low value avalaibility, and get the highest objective value RPN 441 on a 40 point damage to component Servo Off. Solutions to make improvements to enable the Total Productive Maintenance in which includes Autonomous Maintenance. Keywords: Total Productive Maintenance (TPM), Overall Equipment Efectiveness (OEE), Autonomous Maintenance, Failure Mode and Effect Analysis (FMEA)